Comparison of the effects of voluntary termination of pregnancy and uterine evacuation for medical reasons on female sexual function. (April 2016) - Dundar, B.; Dilbaz, B.; Karadag, B.
Abstract: Objective: A wide spectrum of emotions are experienced during abortion, including anxiety, sadness and grief, guilt, pessimism about future pregnancies, disturbed self-perception and loss of confidence in intimate relationships. This study aimed to compare the short-term effects of legal voluntary termination of pregnancy with uterine evacuation for medical reasons on female sexual function. Study design: The study group was comprised of 50 patients admitted to the Family Planning Clinic for legal voluntary termination of pregnancy <10 weeks of gestation, and the control group was comprised of 50 patients who underwent manual vacuum aspiration of the products of conception for medical reasons (e.g. inevitable abortion, incomplete abortion, fetal abnormality and teratogenic drug use). Female sexual function in the two groups was evaluated using the Golombok–Rust Inventory of Sexual Satisfaction (GRISS). GRISS scores immediately before and 3 months after termination of pregnancy were compared within each group and between the two groups. Results: Mean total GRISS scores before and after termination of pregnancy were 5.33 and 8.12 in the study group, and 6.02 and 6.4 in the control group, respectively ( p  < 0.05). The increase in GRISS scores for both groups indicated deterioration in sexual function ( p  = 0.000 and p  = 0.016, respectively). Three months after termination of pregnancy, the total GRISS score was significantly higher in the study group compared with the control group (8.12 vs 6.4, p  < 0.05). Conclusion: Female sexual dysfunction is a complicated concept that is affected by multiple factors over a woman's lifetime. It is important to consider female sexual function as a part of reproductive health, with a close relationship with contraception. As such, patients should receive counselling about sexual function and contraception as part of comprehensive abortion care.